PARAMETER RUMEN TERHADAP TONGKOL JAGUNG AMOFER MENGGUNAKAN STARTER KOMERSIAL DAN UREA PADA LEVEL YANG BERBEDA SECARA IN VITRO - Restuti Fitria; Novita Hindratiningrum (UNU Purwokerto, 2023)
This research aimed to evaluate the levels of addition of M21 Decomposer (MD) and urea (U) to fermented products (concentrations of VFA and NH3) in the rumen. This research used an experimental method with a completely randomized design (CRD). The treatment in this research was the addition of MD and U at different levels (R0 = corn cob without amofer / control; R1 = corn cob amofer with 0.04% MD + 3% U; R2 = corn cob amofer with 0.06% MD + 3% U; R3 = corn cob amofer with 0.04% MD + 5% U; and R4 = corn cob amofer with 0.06% MD + 5% U). The results showed that treatment had no significant effect (P> 0.05) on the concentration of VFA and NH3. However, the results showed that the NH3 concentration tended to increase along with the increasing addition of urea. The conclusion is that the addition of MD and U at the level used has not been able to increase the concentration of VFA and NH3.